Efeito da desnutrição protéica pré e pós-natal sobre a morfologia, a diferenciação e o metabolismo do tecido muscular estriado esquelético em ratos - Alves, Alessandra Pires [UNIFESP] (2008)
OBJECTIVE: To study the contractile properties, metabolism and morphological characteristics of muscles submitted to prenatal and postnatal protein malnutrition. METHODS: Animals were distributed into two groups: Control, normoprotein diet (CG; n = 15; 5/5/5), and Malnourished, hypoprotein diet (MG; n = 15; 5/5/5), and examined on the 7th, 14th, and 28th days of the experiment. Total body mass, weight, and the contractile properties and morphology of the anterior tibial muscle were assessed. Several 8 µm-thick tissue samples were taken from 7, 14, and 28 day old rats and stained with HE or subjected to NADH-TR or m-ATPase (pH = 4.4) techniques. RESULTS: Body and muscle weight were lower in the malnourished group. On the 7th day of malnutrition, muscle samples exhibited fibers with smaller diameter, higher polymorphism and higher endomysial conjunctive tissue content. Histochemical methods were unable to precisely determine the types of fiber present. On the 14th day, there were smaller muscle fibers, more polymorphism, many of them with central nuclei and moderate endomysial conjunctive tissue content. With reference to contractile properties, the m-ATPase reaction identified both slow and fast fibers. The NADH-TR reaction revealed the following types of fiber: slow oxidative (SO), fast oxidative glycolytic (FOG) and fast glycolytic (FG). On the 28th day smaller, bunched muscle fibers varying shapes. All three types of fiber exhibited unclear recognition limits with respect to contraction and metabolism. CONCLUSION: Our experimental results suggest that, in addition to the reduction in numbers of fibers, malnutrition retards the differentiation of the morphological, metabolic, and contractile characteristics of skeletal muscle fibers in growing rats.